The Influence of Learning Motivation, Parental Support and Facilities and Infrastructure on Student Learning Achievement Mediated by Online Learning Models (Study at SMPN 5 Tanta, Tabalong Regency During the Covid 19 Pandemic) - Eka Noresda; Lanny Purnama Kosasi (Jurnal Multidisiplin Sahombu, 2023)
The success of learning during the Covid-19 period depends on the discipline of all parties. Therefore, the school here needs to create a scheme by compiling good management in fostering the learning system. This is done by creating a systematic, structured schedule and facilitating communication between parents and the school so that their children who study at home can be monitored effectively. Thus, brave learning as an effective solution in learning at home to break the chain of Covid-19, physical distance (maintaining a safe distance) is also a consideration in choosing this learning. Good cooperation between teachers, students, parents of students and the school is a determining factor for more effective learning. This must be supported by good learning methods because without good learning methods, schools will not achieve their goals. For that, of course, students need good learning methods to be able to achieve learning achievements. To achieve good achievement, learning motivation, parental support and infrastructure greatly influence. In addition, the learning method obtained by students is an important aspect, because it can have an impact on better achievement. Therefore, this study aims to determine the effect of learning motivation, parental support, facilities and infrastructure and learning methods on student learning achievement. The population in this study were teachers, parents of students and students at SMP Negeri 5 Tanta, Tabalong Regency, totaling 43 people. The researcher used a saturated sampling technique, meaning that all populations can be used as samples in this study. Data analysis in this study used a path analysis model using software Smart PLS, because of the presence of intervening variables in this research model. The results of this study indicate that learning motivation, parental support, and facilities and infrastructure have been proven to have a significant positive effect on learning methods. Learning motivation, parental support, facilities and infrastructure and learning methods have been proven to have a significant positive effect on learning achievement.